Trends and derteminants of adelescent fertility in Zimbabwe - Dzumbunu, Silinganisiwe (Centre for Actuarial Research (CARE), 2020)
This study examines the trends and socio-demographic determinants of adolescent fertility in Zimbabwe. The study uses all six ZDHS surveys that have been conducted for Zimbabwe between 1988 and 2015. Adolescent fertility trends were examined using age-period and cohort-period fertility estimates. The Poisson regression model and the tfr2 module developed by Schoumaker (2013) are used to calculate age-period fertility estimates (ASFRS). Cohort- period fertility rates (CPFRs) were calculated using a method developed by Moultrie, Dorrington, Hill et al. (2013b). ASFRs and CPFRs trends were constructed for the 15 year prior to each ZDHS survey. The trends in both the ASFRS and CPFRs showed that total fertility and 5-year fertility levels above the age of 20 years has significantly declined from the late 1980’s to the mid to around 2010 and since 2010 the fertility levels in these age groups have remained almost constant. However, fertility levels in the 15-19 years age group have been fluctuating around 110 births per 1000 women with no sign of a declining trend since around 1985. The second part of the analysis investigated the socio-demographic factors that have been influencing adolescent fertility in Zimbabwe. Two multiple logistic regression models based on the McDevitt, Adlakha, Fowler et al. (1996) model of proximate determinants of adolescence fertility were used to examine the association between eight socio-demographic factors and adolescent fertility. Results of logistic regression analysis revealed that a significant association exists between adolescent fertility and use of contraception, age at first sex, age of the respondent, marital status, highest level of education attended and employment status at the time of the survey. The odds of giving birth prior to each survey were higher among adolescents who had ever used contraception, initiated sexual activities at a very young age, older adolescents, were married, with low level of education ever attended and those who were unemployed at the time of the survey. This study concluded that adolescent (15-19 years) fertility rates have remained high despite a decrease in all the other age specific and total fertility rates. There is need to introduce and evaluate existing policies and programs that focus on improving socio-economic conditions of adolescents women in Zimbabwe.